Ekstraksi Pektin dari Kulit Buah Coklat dengan Pelarut Asam Sitrat - S Susilowat (Eksergi)
Cocoa (Theobroma cacao) is a plant which is often found Indonesia, especially from plantations. Cocoa is into 3 sections, that is peel, fruit’s flesh and seeds. But so far in its use only cocoa flesh and seeds are taken to be used. While the peel is less utilized, becames a lot of waste and is usually used as animal’s feed. Cocoa peel is a source of pectin. Pectin in the food industry is a thickener and an additive in manufacturing jam, jelly, marmalade etc. Process of taking pectin from cocoa peel is done by extraction with citric acid solvent at operating condition pH 3, material and solvent ratio of 1:2, 1:14, 1:16, 1:18, 1:20, operation time of 75 minutes, 100 minutes, 125 minutes, 150 minutes, and 175 minutes, at 80oC and washing with alcohol and without alcohol. From the result of the research it is obtained that methoxyl content is 42.80% on washing with alcohol and 42.86 % on washing without alcohol. The best comparison of solvent is at 1:18 and 150 minutes of extraction time. Treatment on washing with alcohol and without alcohol produces methoxyl content which is almost same, but is terms of color on pectin washing with alcohol produces a clean and white color.